We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+2
255
1
avatar+557 

https://vle.mathswatch.co.uk/images/questions/question2233.png

need help quick plz

 Feb 10, 2018

Best Answer 

 #1
avatar+8095 
+2

 

a)   This must mean find  f( g(x) ) .

 

f(x)   =   2x - 3

 

f( g(x) )   =   2( g(x) ) - 3

                                            And  g(x)  =  x2 + 1 , so we can replace  g(x)  with  x2 + 1 .

f( g(x) )   =   2(x2 + 1) - 3

 

f( g(x) )   =   2x2 + 2 - 3

 

f( g(x) )   =   2x2 - 1

 

b)   Find  g( f(x) ) .

 

g(x)   =   x2 + 1

 

g( f(x) )   =   ( f(x) )2 + 1

                                            And  f(x)  =  2x - 3 , so we can replace  f(x)  with  2x - 3 .

g( f(x) )   =   (2x - 3)2 + 1

 

g( f(x) )   =   (2x - 3)(2x - 3) + 1

 

g( f(x) )   =   4x2 - 12x + 9 + 1

 

g( f(x) )   =   4x2 - 12x + 10

 Feb 10, 2018
 #1
avatar+8095 
+2
Best Answer

 

a)   This must mean find  f( g(x) ) .

 

f(x)   =   2x - 3

 

f( g(x) )   =   2( g(x) ) - 3

                                            And  g(x)  =  x2 + 1 , so we can replace  g(x)  with  x2 + 1 .

f( g(x) )   =   2(x2 + 1) - 3

 

f( g(x) )   =   2x2 + 2 - 3

 

f( g(x) )   =   2x2 - 1

 

b)   Find  g( f(x) ) .

 

g(x)   =   x2 + 1

 

g( f(x) )   =   ( f(x) )2 + 1

                                            And  f(x)  =  2x - 3 , so we can replace  f(x)  with  2x - 3 .

g( f(x) )   =   (2x - 3)2 + 1

 

g( f(x) )   =   (2x - 3)(2x - 3) + 1

 

g( f(x) )   =   4x2 - 12x + 9 + 1

 

g( f(x) )   =   4x2 - 12x + 10

hectictar Feb 10, 2018

17 Online Users

avatar
avatar